PENGARUH SARANA PRASARANA SEKOLAH DAN KOMUNIKASI INTERPERSONAL TERHADAP KINERJA GURU - Elfiza; Gusnardi, Sumarno (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article examines the influence of school infrastructure facilities and interpersonal communication on teacher performance in SMA Muhammadiyah all over Riau Province. The field observation showed that teachers cannot manage and utilize the learning infrastructure facilities. It is because of the lack of teachers’ understanding of using learning media. In addition, there is also conflict between fellow colleagues due to the competition, and it makes the working to be uncomfortable and conducive. The study described in this article used a research design in the form of an influential study, which is to determine the three variables, the independent variables, namely free school infrastructure (X1) and interpersonal communication (X2), and the dependent variable, teacher performance (Y). The study population was 5 Muhammadiyah Senior High Schools in Riau Province, namely Muhammadiyah Tembilahan Senior High School, Bagan Batu Muhammadiyah Senior High School, Muhammadiyah Rambah Senior High School, Bangkinang Muhammadiyah Senior High School, and Dumai City Muhammadiyah Senior High School. The sample involved 96 students. The data collection technique used a questionnaire. The results showed that there was an influence between school infrastructure facilities mutually on the performance of Muhammadiyah Senior High School teachers in Riau Province in the percentage of 66,9% of 100% as an expected percentage score.